The importin- P446L dominant-negative mutant protein loses RanGTP binding ability and blocks the formation of intact nuclear envelope. - Timinszky, G.; Tirian, L.; Nagy, F.T.; Toth, G.; Perczel, A.; Kiss-Laszlo, Z.; Boros, I.; Clarke, P.R.; Szabad, J. (Journal of Cell Science, 2002)
Three of the four independently induced Ketel(D) dominantnegative female sterile mutations that identify the Drosophila importin-beta gene, originated from a C4114--> T transition and the concurrent replacement of Pro446 by Leu (P446L). CD spectroscopy of representative peptides with Pro or Leu in the crucial position revealed that upon the Pro-->Leu exchange the P446L mutant protein loses flexibility and attains most likely an open conformation. The P446L mutation abolishes RanGTP binding of the P446L mutant form of importin-beta protein and results in increased RanGDP binding ability. Notably, the P446L mutant importin-beta does not exert its dominant-negative effect on nuclear protein import and has no effect on mitotic spindle-related functions and chromosome segregation. However, it interferes with nuclear envelope formation during mitosis-to-interphase transition, revealing a novel function of importin-beta.